1982
DOI: 10.1093/nar/10.2.689
|View full text |Cite
|
Sign up to set email alerts
|

The primary structures of two leghemoglobin genes from soybean

Abstract: We present the complete nucleotide sequences of two leghemoglobin genes isolated from soybean DNA. Both genes contain three intervening sequences which interrupt the two coding sequences in identical positions. The 5' and 3' flanking sequences in both genes contain conserved sequences similar to those found in corresponding positions in other eukaryotic genes. Thus, the general DNA sequence organization of these plant genes is similar to that of other eukaryotic genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(67 citation statements)
references
References 19 publications
5
62
0
Order By: Relevance
“…One notorious example is the legume haemoglobin, supposed to be the result of horizontal transfer from animals by means of a viral carrier (Hyldig-Nielsen et al, 1982; but see Appleby et al, 1990). In such cases the sequence of the gene being studied is incongruent with that of the organism that carries it.…”
Section: Homology In Molecular and Morphological Data: Is There A Funmentioning
confidence: 99%
“…One notorious example is the legume haemoglobin, supposed to be the result of horizontal transfer from animals by means of a viral carrier (Hyldig-Nielsen et al, 1982; but see Appleby et al, 1990). In such cases the sequence of the gene being studied is incongruent with that of the organism that carries it.…”
Section: Homology In Molecular and Morphological Data: Is There A Funmentioning
confidence: 99%
“…DNA sequencing studies suggest that legume hemoglobins and animal globins share the same genetic origin and it has been suggested that the gene for legume hemoglobm was transferred to legumes from another eukaryote outside the plant kingdom, relatively recently in evolutionary history [6,7]. However, the identification of hemoglobin m Parasponra [3], Casaurrna and other nonlegume species [g-10] questions this proposal and suggests that hemoglobin genes may have persisted in many plant families since divergence of the plant and animal lines some 1000 million years ago [I ,7].…”
Section: Introductionmentioning
confidence: 99%
“…The A+T content of the introns is similar to that in soybean proteins, but is considerably higher than those of non-plant species. Two CCAAT box-like sequences are located at positions -67 (CCAT) and -74 (CCAAAT), similar to those of soybean leghemoglobin genes [41]. Zein, the major storage prolamin storage protein of maize [42] is encoded by a family of highly similar genes bearing a TATA motif at -32, similar to that of most eukaryotes.…”
Section: Phaseolin Gene Structurementioning
confidence: 99%